1990
DOI: 10.1037/h0078936
|View full text |Cite
|
Sign up to set email alerts
|

Canadian federal elections: Motive profiles and integrative complexity in political speeches and popular media.

Abstract: Materials from the popular media and the speeches of federal party leaders, appearing approximately 2 months before the election in the 10 Canadian federal election years 1945-74, were analyzed lor motive imagery (need for achievement, power, and affiliation) and integrativu complexity. Media items were significantly higher in affiliation and power imagery and significantly lower in achievement than leaders' speeches. There was a significant correlation between the overall imagery content (motive richness) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Yet we also make a number of unique contributions. Prior research has manually coded the integrative complexity of relatively small samples of elite discourse, typically that of world leaders (e.g., Conway, Suedfeld, & Clements, ; Suedfeld, ; Suedfeld et al., ; Tetlock, , ; Thoemmes & Conway, ) and U.S. Supreme Court Justices (e.g., Gruenfeld, ; Gruenfeld & Preston, ; Tetlock et al., ), all of whom speak primarily to diverse constituencies within heterogeneous electorates or to ideologically divided colleagues. We move beyond this approach through the use of a relatively large sample of computer‐coded blog posts and through modeling integrative complexity as an outcome of opinion‐leadership style.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet we also make a number of unique contributions. Prior research has manually coded the integrative complexity of relatively small samples of elite discourse, typically that of world leaders (e.g., Conway, Suedfeld, & Clements, ; Suedfeld, ; Suedfeld et al., ; Tetlock, , ; Thoemmes & Conway, ) and U.S. Supreme Court Justices (e.g., Gruenfeld, ; Gruenfeld & Preston, ; Tetlock et al., ), all of whom speak primarily to diverse constituencies within heterogeneous electorates or to ideologically divided colleagues. We move beyond this approach through the use of a relatively large sample of computer‐coded blog posts and through modeling integrative complexity as an outcome of opinion‐leadership style.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on integrative complexity and ideology have focused on political elites, such as world leaders (e.g., Conway, Suedfeld, & Clements, ; Suedfeld, ; Suedfeld, Bluck, Ballard, & Baker‐Brown, ; Suedfeld, Cross, & Brcic, ; Tetlock, , ; Thoemmes & Conway, ) and Supreme Court Justices (Gruenfeld, ; Gruenfeld & Preston, ; Tetlock et al., ), all of whom are tasked with addressing heterogeneous publics or ideologically partisan colleagues. Researchers have not yet examined the discourse of nonelites directed at like‐minded communities—a dominant feature of the contemporary political landscape that potentially introduces important shifts within group dynamics.…”
Section: Motivated Social Cognition and Ideologymentioning
confidence: 99%
“…In fact, from this perspective simplicity may be viewed as not only cognitively efficient, but also as representing a more factually and morally correct view of the world, whereas complexity may be associated with confusion and vacillation. Certainly, some recent evidence suggests that there may be ideologically based differences in complexity (Suedfeld, Bluck, Ballard, & Baker-Brown, 1990;Tetlock, 1984).…”
mentioning
confidence: 99%
“…Suedfeld and his colleagues have developed a technique for scoring the degree of cognitive complexity of political leaders. Suedfeld has co-authored articles on the topic of integrative complexity (Suedfeld, Bluck, Ballard, & Baker-Brown, 1990;Suedfeld, Bluck, Loewen, & Elkins, 1994;Suedfeld, Conway, & Eichhorn, 2001;Suedfeld & Tetlock, 1977;Suedfeld, Wallace, & Thachuk, 1993;Wallace, Suedfeld, & Thachuk, 1996). Suedfeld has also written on the political psychology of torture (1990), on the positive face of stress (Suedfeld, 1997), on the psychology of environmental ideology (LaVallee & Suedfeld, 1997), and on the vexed issue of value neutrality versus commitment in political psychological research (Suedfeld & Tetlock, 1991).…”
Section: The Political Psychology Of Cognition and Decisionmentioning
confidence: 99%
“…Using speeches coded from Canadian Hansard from 1948 to 1988, the authors reported broad support for the hypothesis. Among Suedfeld's students, Ballard (1983;Ballard & Suedfeld, 1988;Suedfeld et al, 1990) has written directly on Canadian prime ministers. This particular application of integrative complexity to Canada's political leaders achieved national attention in 1998 with the publication of a large feature article in Canada's national newspaper, the Globe and Mail (Schachter, 1998).…”
Section: The Political Psychology Of Cognition and Decisionmentioning
confidence: 99%